Students’ Attitude on The Use of Facebook And Blog In Writing Class and Their Writing Competence - Irfan Rifai (Lingua Cultura, 2010)
Article aims to investigate the relationship between students’ attitudes on the use of Facebook and blog as learning tools in writing class. Two groups of students were made as experimental and control group. The experimental group used Facebook and blog in as learning tools for thirteen sessions while the control group only used Binusmaya, local multi channel learning. It was assumed that Facebook and blog would be able to help students in three level of writing mastery: the vocabulary, the accuracy and the fluency in writing. Students’ attitudes were gathered through survey and the results compared to their final test scores. The result shows that students’ lack of enthusiasm was in line with students’ level of achievement in writing and that Facebook and blog did not give significant influence on improving students’ writing competence.